Misinformation about contraceptive methods and their impact on teenage pregnancies (Research, Society and Development, 2023)
Adolescence is a period marked by changes, characterizing the transition from childhood to adulthood. Together with this stage, sexuality is an important component of the adolescent's identity and its exercise can be marked by discoveries and conflicts. The purpose of the work presented was to carry out a bibliographical review seeking to investigate the association between the occurrence of pregnancy in adolescence and lack of knowledge about sexuality and the use of contraceptive methods available in Brazil and to give visibility to the facilitating factors regarding the occurrence of early pregnancy. This is an integrative literature review, in which the bibliographic survey was carried out through the CAPES Portal de Periódicos in the period between February and March 2023. After the complete reading of the 26 articles, considering the eligibility criteria, 19 were excluded , which did not present suitable methods and/or results for this review, and 6 articles were chosen for the integrative review. Considering that early pregnancy is a huge public health challenge and that it causes a great psychological and socioeconomic impact, it is concluded that the objectives of the study were achieved, regarding the observation of impacting factors for a teenage pregnancy. Lack of knowledge about sexuality and about the benefits and myths of contraceptive methods in adolescence, inadequate counseling, low socioeconomic status, daughters of women who were teenage mothers, sociocultural taboos, legal restrictions, moralistic attitudes towards sexuality, are related to early pregnancy , associated with the vulnerabilities of this phase of life.